Highly efficient charged cleaning protective composite spray
Patent Information
- Application Number
- CN202611198671.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-08
- Publication Date
- 2026-10-20
AI Technical Summary
1、本申请利用介孔二氧化硅与ZIF-8复合,形成介孔二氧化硅为核、ZIF-8为壳层的结构,ZIF-8规则的孔道为醇分子提供了选择性吸附和传输通道,而二氧化硅的亲水介孔为水分子提供了快速释放路径,这种双孔道结构解决了传统含水清洗剂因醇水挥发速率差异导致的水渍残留问题,显著提升了清洗后的绝缘恢复速度与表面清洁度。
Abstract
Description
Technical Field
[0001] This application relates to the field of cleaning agent technology, and more specifically, to a high-efficiency electrostatic cleaning and protective composite spray. Background Technology
[0002] Live-line insulated equipment is often contaminated by industrial dirt or natural pollutants such as salt, dust, and bird droppings. In dry conditions, these contaminants have high resistance, but in environments with high humidity, the surface contaminants become wet, causing a dramatic increase in surface conductivity and leakage current. This significantly reduces the flashover voltage of the insulated equipment, potentially even causing flashover at operating voltage, thus affecting the safe operation of the power system. Compared to traditional methods such as dry cleaning, air blowing, and water rinsing, using chemical cleaning agents for live-line chemical cleaning of power grid equipment can effectively solve this problem.
[0003] In the prior art, Chinese invention patent application number CN202510743579.9 discloses an insulating and electrically charged cleaning agent and its preparation method. The insulating and electrically charged cleaning agent includes the following components: low carbon alcohol, compound nonionic surfactant, nano silica dispersion, antistatic regulator and antioxidant stabilizer.
[0004] Regarding the aforementioned prior art, the inventors believe that the volatilization rate of low-carbon alcohols decreases significantly under high humidity conditions, and the insulation recovery time after cleaning is prolonged, affecting the efficiency of live-line work. Summary of the Invention
[0005] To address the problems in the prior art, this application provides a high-efficiency electrostatic cleaning and protective composite spray.
[0006] The high-efficiency electrostatic cleaning and protective composite spray provided in this application adopts the following technical solution: High-efficiency electrical cleaning and protective compound spray, comprising the following raw materials in parts by weight: 20-40 parts of low carbon alcohol, 5-15 parts of nonionic surfactant, 0.1-0.3 parts of SiO2@ZIF-8 porous material, 1-3 parts of antistatic regulator, 0.05-0.2 parts of antioxidant stabilizer, and 40-75 parts of water.
[0007] By adopting the above technical solution, a mixed solvent system is formed by low-carbon alcohol and water. The low-carbon alcohol acts as the main solvent to dissolve oil stains and evaporate rapidly. Nonionic surfactants effectively reduce surface tension and enhance the emulsification and dispersion capabilities for oily and polar dirt. The SiO2@ZIF-8 porous material selectively adsorbs and slowly releases low-carbon alcohol through the ZIF-8 shell, while mesoporous silica simultaneously adsorbs and releases water molecules. This achieves gradient evaporation control of low-carbon alcohol slow release and water molecule synchronization, effectively solving the problem of water stain residue caused by the difference in alcohol evaporation rate in traditional water-based cleaning agents. At the same time, it prolongs the wetting time of the liquid film on the equipment surface, providing a more abundant window for surfactants to penetrate and emulsify stubborn dirt, significantly improving the surface cleanliness and insulation speed after cleaning. In addition, the high insulation properties of ZIF-8 and SiO2 themselves further enhance the electrical safety of the system.
[0008] Optionally, the preparation method of the SiO2@ZIF-8 porous material includes the following steps: S1. Disperse mesoporous silica in a zinc nitrate hexahydrate ethanol solution, stir and evaporate the solvent at 60-70℃, and calcine at 550-600℃ for 2-4 hours to obtain MSN-ZnO. The mass ratio of the mesoporous silica to the zinc nitrate hexahydrate ethanol solution is 1:35-45. S2. The MSN-ZnO and nitrogen-sulfur co-doped carbon quantum dots are dispersed in a 2-methylimidazolium methanol solution, stirred at 23-27°C, centrifuged, washed, and dried to obtain SiO2@ZIF-8 porous material. The mass ratio of MSN-ZnO to 2-methylimidazolium methanol solution is 1:500-700.
[0009] By employing the above technical solution, the ZIF-8 shell has a hydrophobic microporous structure, exhibiting selective and preferential adsorption capacity for low-carbon alcohol molecules, while the mesoporous silica has a hydrophilic mesoporous structure, possessing a strong adsorption affinity for water molecules. Together, they form a bilayer adsorption system with an outer hydrophobic and an inner hydrophilic structure, achieving selective separation and cascade adsorption of alcohol and water molecules. During the evaporation stage, the ZIF-8 shell utilizes its confinement effect, with its pore size comparable to the size of low-carbon alcohol molecules, to strongly bind the adsorbed low-carbon alcohol molecules, achieving controlled release. Meanwhile, the mesoporous silica core has relatively weak adsorption of water molecules, resulting in a faster water molecule release rate. Together, they achieve controlled release of low-carbon alcohols, providing time for the preferential evaporation of the fluorinated co-solvent. Subsequently, the mesoporous silica core rapidly releases the adsorbed water molecules, ensuring thorough surface drying. Finally, the porous material is added to the composite spray, shortening the evaporation time in environments with high relative humidity.
[0010] Optionally, the method for preparing the nitrogen-sulfur co-doped carbon quantum dots includes the following steps: Citric acid and thiourea were ultrasonically dissolved in N,N-dimethylformamide to prepare a transparent solution. The transparent solution was then subjected to a hydrothermal reaction at 180-200℃ for 12-16 hours. After filtration, dialyzing, and freeze-drying, nitrogen-sulfur co-doped carbon quantum dots were obtained.
[0011] By adopting the above technical solution and introducing nitrogen-sulfur co-doped carbon quantum dots, the porous material is upgraded from a simple adsorption and slow-release carrier to a composite volatile control material with photothermal conversion function. Using citric acid as carbon source and thiourea as dopant, nitrogen-sulfur co-doped carbon quantum dots are prepared through hydrothermal reaction. Nitrogen- and sulfur-containing functional groups are introduced on the surface, which significantly enhances the light absorption capacity. The carbon quantum dots are encapsulated in situ on the surface of the porous material, thereby efficiently converting the absorbed light energy into heat energy, generating a local heating effect, forcibly accelerating the evaporation of residual liquid, and the photothermal effect greatly shortens the volatilization time. At the same time, the gentle heat generated by photothermal treatment helps to remove moisture from the surface of the insulating component, further improving the insulation recovery speed.
[0012] Optionally, the mass ratio of citric acid, thiourea and N,N-dimethylformamide is 1:1.5-2:10-15.
[0013] Optionally, the lower alcohol is selected from one or more of isopropanol, ethanol, n-propanol and methanol.
[0014] Optionally, the antistatic agent is selected from one or more of cationic antistatic agents, zwitterionic antistatic agents, and nonionic antistatic agents.
[0015] By adopting the above technical solution, a hydrophilic conductive adsorption layer is formed on the surface of the equipment after spraying. The hydrophobic groups in the molecules are anchored to the surface of the insulating material, while the hydrophilic groups face the air and absorb trace amounts of moisture from the environment to form a continuous thin water film. This provides a conductive path for the rapid leakage and dissipation of static charge, preventing secondary adsorption of dust, partial discharge, or even flashover accidents caused by static electricity accumulation.
[0016] Optionally, the antioxidant stabilizer is selected from one or more of phenolic antioxidants, amine antioxidants, and thioether antioxidants.
[0017] By adopting the above technical solution, the composite spray plays a core role in delaying oxidation and deterioration and extending shelf life, and is especially suitable for high temperature or long-term storage scenarios.
[0018] Optionally, the nonionic surfactant is selected from one or both of fatty alcohol polyoxyethylene ethers and alkyl glycosides.
[0019] In summary, this application has the following beneficial effects: 1. This application utilizes mesoporous silica and ZIF-8 composite to form a structure with mesoporous silica as the core and ZIF-8 as the shell. The regular channels of ZIF-8 provide selective adsorption and transport channels for alcohol molecules, while the hydrophilic mesopores of silica provide a rapid release path for water molecules. This dual-channel structure solves the problem of water stain residue caused by the difference in evaporation rates of alcohol and water in traditional water-containing cleaning agents, and significantly improves the insulation recovery speed and surface cleanliness after cleaning.
[0020] 2. In this application, citric acid is used as a carbon source and thiourea is used as a sulfur source to prepare nitrogen-sulfur co-doped carbon quantum dots, upgrading the porous material into a composite volatile control material with photothermal conversion function, and using the photothermal effect to significantly shorten the volatilization time.
[0021] 3. In this application, a unique gradient volatilization regulation mechanism is constructed by synergistic compounding of low carbon alcohol, nonionic surfactant, functional additives and SiO2@ZIF-8 porous material. The ZIF-8 shell selectively adsorbs and slowly releases low carbon alcohol, while the mesoporous silica simultaneously adsorbs and releases water molecules, achieving the effect of slow release of low carbon alcohol and simultaneous release of water molecules. This effectively solves the problem of water stain residue caused by the difference in volatilization between alcohol and water in traditional water-containing cleaning agents, and shortens the volatilization time in high humidity environments. Detailed Implementation
[0022] The following embodiments provide a further detailed description of this application.
[0023] Preparation example of nitrogen-sulfur co-doped carbon quantum dots Source of raw materials: Citric acid is selected from Guangzhou Ruicheng Chemical Co., Ltd., and its product number is anhydrous citric acid.
[0024] Preparation Example 1-1: 1g of citric acid and 2g of thiourea were ultrasonically dissolved in 15g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 200℃ for 16h. The solution was filtered through a 0.22um microporous membrane and then transferred to a dialysis bag with a molecular weight cutoff of 1000Da for dialysis for 48h. The solution was then freeze-dried at -40℃ for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0025] Preparation Example 1-2: 1g of citric acid and 1.8g of thiourea were ultrasonically dissolved in 13g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 190℃ for 14h. The solution was filtered through a 0.22um microporous membrane and then transferred to a dialysis bag with a molecular weight cutoff of 1000Da for dialysis for 48h. The solution was then freeze-dried at -40℃ for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0026] Preparation Examples 1-3: 1g of citric acid and 1.5g of thiourea were ultrasonically dissolved in 10g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 180℃ for 12h. The solution was filtered through a 0.22um microporous membrane and then transferred to a dialysis bag with a molecular weight cutoff of 1000Da for dialysis for 48h. The solution was then freeze-dried at -40℃ for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0027] Preparation Examples 1-4: 1g of citric acid and 1g of thiourea were ultrasonically dissolved in 15g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 200℃ for 16h. The solution was filtered through a 0.22µm microporous membrane and then transferred to a dialysis bag with a molecular weight cutoff of 1000Da for dialysis for 48h. The solution was then freeze-dried at -40℃ for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0028] Preparation Examples 1-5: 2g of citric acid and 1g of thiourea were ultrasonically dissolved in 8g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 200℃ for 16h. The solution was filtered through a 0.22µm microporous membrane and then transferred to a dialysis bag with a molecular weight cutoff of 1000Da for dialysis for 48h. The solution was then freeze-dried at -40℃ for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0029] Preparation Examples 1-6: The difference from Preparation Example 1-1 is that thiourea was not added. 1g of citric acid was ultrasonically dissolved in 15g of N,N-dimethylformamide to obtain a transparent solution. The transparent solution was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 200°C for 16h. The solution was then filtered through a 0.22µm microporous membrane. The filtered solution was transferred to a dialysis bag with a molecular weight cutoff of 1000Da and dialyzed for 48h. Finally, it was freeze-dried at -40°C for 14h to obtain nitrogen-sulfur co-doped carbon quantum dots.
[0030] Example of SiO2@ZIF-8 porous material preparation Source of raw materials: Mesoporous silica is selected from Hangzhou Jikang New Materials, with product number SS-S05J.
[0031] Preparation Example 2-1: S1. 1g of mesoporous silica was added to 45g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 70℃, and calcined at 600℃ for 4h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0032] S2. 1g MSN-ZnO and 0.3g nitrogen-sulfur co-doped carbon quantum dots were added to 700g 2-methylimidazolium methanol solution, stirred at 27°C for 48h, centrifuged at 8000rpm, washed three times with ethanol, and dried at 60°C for 8h to obtain SiO2@ZIF-8 porous material; the nitrogen-sulfur co-doped carbon quantum dots were prepared by preparation example 1-1; the 2-methylimidazolium methanol solution was prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0033] Preparation Example 2-2: S1, 1g of mesoporous silica was added to 40g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 65℃, and calcined at 580℃ for 3h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0034] S2. 1g MSN-ZnO and 0.2g nitrogen-sulfur co-doped carbon quantum dots were added to 600g 2-methylimidazolium methanol solution, stirred at 27°C for 30h, centrifuged at 8000rpm, washed three times with ethanol, and dried at 60°C for 8h to obtain SiO2@ZIF-8 porous material; nitrogen-sulfur co-doped carbon quantum dots were prepared from preparation examples 1-2; 2-methylimidazolium methanol solution was prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0035] Preparation Example 2-3: S1, 1g of mesoporous silica was added to 35g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 60℃, and calcined at 550℃ for 2h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0036] S2. 1g MSN-ZnO and 0.15g nitrogen-sulfur co-doped carbon quantum dots were added to 500g 2-methylimidazolium methanol solution, stirred at 23°C for 24h, centrifuged at 8000rpm, washed three times with ethanol, and dried at 60°C for 8h to obtain SiO2@ZIF-8 porous material; the nitrogen-sulfur co-doped carbon quantum dots were prepared according to preparation examples 1-3; the 2-methylimidazolium methanol solution was prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0037] Preparation Example 2-4: S1, 0.5g of mesoporous silica was added to 45g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 70℃, and calcined at 600℃ for 4h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0038] S2. 1g MSN-ZnO and 0.3g nitrogen-sulfur co-doped carbon quantum dots were added to 700g 2-methylimidazolium methanol solution, stirred at 27°C for 48h, centrifuged at 8000rpm, washed three times with ethanol, and dried at 60°C for 8h to obtain SiO2@ZIF-8 porous material; the nitrogen-sulfur co-doped carbon quantum dots were prepared by preparation example 1-1; the 2-methylimidazolium methanol solution was prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0039] Preparation Example 2-5: S1, 1g of mesoporous silica was added to 45g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 70℃, and calcined at 600℃ for 4h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0040] S2. 1g MSN-ZnO and 0.1g nitrogen-sulfur co-doped carbon quantum dots were added to 700g 2-methylimidazolium methanol solution, stirred at 27℃ for 48h, centrifuged at 8000rpm, washed three times with ethanol, and dried at 60℃ for 8h to obtain SiO2@ZIF-8 porous material; the nitrogen-sulfur co-doped carbon quantum dots were prepared by preparation example 1-1; the 2-methylimidazolium methanol solution was prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0041] Preparation Example 2-6: The difference from Preparation Example 2-1 is that the nitrogen-sulfur co-doped carbon quantum dots were prepared in Preparation Example 1-4.
[0042] Preparation Example 2-7: The difference from Preparation Example 2-1 is that the nitrogen-sulfur co-doped carbon quantum dots were prepared in Preparation Example 1-5.
[0043] Preparation Example 2-8: The difference from Preparation Example 2-1 is that the nitrogen-sulfur co-doped carbon quantum dots were prepared by Preparation Example 1-6.
[0044] Preparation Example 2-9: The difference from Preparation Example 1-1 is that nitrogen and sulfur co-doped carbon quantum dots were not added. S1, 1g of mesoporous silica was added to 45g of zinc nitrate hexahydrate ethanol solution, ultrasonically dispersed at 300W for 40min, the solvent was evaporated by stirring at 70℃, and calcined at 600℃ for 4h to obtain MSN-ZnO; the zinc nitrate hexahydrate ethanol solution was prepared by dissolving zinc nitrate hexahydrate in 75wt% ethanol solution, and the mass ratio of zinc nitrate hexahydrate to 75wt% ethanol solution was 1:15.
[0045] S2. Add 1g MSN-ZnO to 700g 2-methylimidazolium methanol solution, stir at 27℃ for 48h, centrifuge at 8000rpm, wash three times with ethanol, and dry at 60℃ for 8h to obtain SiO2@ZIF-8 porous material; the 2-methylimidazolium methanol solution is prepared by mixing 2-methylimidazolium and methanol in a mass ratio of 1:15.
[0046] Example
[0047] Example 1: High-efficiency charged cleaning and protective composite spray, the raw material composition of which is shown in Table 1, the antistatic conditioner is dodecyl betaine; the antioxidant stabilizer is 2,6-di-tert-butyl-p-cresol; the nonionic surfactant is fatty alcohol polyoxyethylene ether; the water is selected from deionized water; The preparation method of this high-efficiency charged cleaning and protective composite spray includes the following steps: SiO2@ZIF-8 porous material was added to a low-carbon alcohol and ultrasonically dispersed at 300W for 30 minutes to obtain a uniform pre-dispersion. Nonionic surfactants were added to the pre-dispersion liquid and stirred for 10 min. Deionized water was added and stirred for another 10 min. Antistatic regulators and antioxidant stabilizers were added and stirred for 15 min to obtain a mixture. The mixture was then transferred to a high-shear dispersion emulsifier and homogenized at 10,000 rpm for 10 min. The SiO2@ZIF-8 porous material was prepared from Preparation Example 2-1.
[0048] Table 1. Raw material ratios of the high-efficiency charged cleaning and protective composite sprays in Examples 1-4. Low alcohols 40 30 25 20 Nonionic surfactants 15 10 8 5 <![CDATA[SiO2@ZIF-8 porous material]]> 0.3 0.25 0.2 0.1 Antistatic agent 3 2 1.5 1 antioxidant stabilizers 0.2 0.15 0.1 0.05 water 75 60 50 40 Example 2: High-efficiency charged cleaning and protective composite spray. The difference from Example 1 is that the SiO2@ZIF-8 porous material is prepared by Example 2-2, and the raw material amounts are shown in Table 1.
[0049] Example 3: High-efficiency charged cleaning and protective composite spray. The difference from Example 1 is that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-3, and the raw material amounts are shown in Table 1.
[0050] Example 4: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the amount of raw materials used is different, as shown in Table 1.
[0051] Example 5: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-4.
[0052] Example 6: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the SiO2@ZIF-8 porous material is prepared by Example 2-5.
[0053] Example 7: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-6.
[0054] Example 8: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-7.
[0055] Example 9: High-efficiency charged cleaning and protective composite spray, the difference from Example 1 is that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-8.
[0056] Example 10: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that the SiO2@ZIF-8 porous material is made from Preparation Examples 2-9.
[0057] Comparative Example Comparative Example 1: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that it does not contain SiO2@ZIF-8 porous material.
[0058] Comparative Example 2: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that it uses mesoporous silica to replace the SiO2@ZIF-8 porous material in an equal amount.
[0059] Comparative Example 3: High-efficiency charged cleaning and protective composite spray, which differs from Example 1 in that it uses ZIF-8 to replace the SiO2@ZIF-8 porous material in equal amounts.
[0060] Performance testing
[0061] The high-efficiency charged cleaning and protective composite spray was prepared according to the methods in the examples and comparative examples, and its performance was tested according to the following methods. The test data are recorded in Table 2.
[0062] 1. Evaporation rate and residual amount determination: Place 10g of the protective composite spray in a silicone rubber container for 1 hour and determine its residual amount.
[0063] 2. Insulation performance test: The dielectric strength is tested by high voltage breakdown test, and should be ≥30kV / mm; 3. Decontamination ability test: Prepare a simulated stain sample, which is a mixture of transformer oil, dust and metal oxide in a ratio of 3:2:1. Apply the mixture evenly to a glass test piece, let it dry, and then spray and wipe it with a cleaning agent. Use a grayscale card to compare the amount of stain residue on the test piece before and after cleaning.
[0064] Table 2 Test data of high-efficiency charged cleaning and protective composite spray Example 1 <![CDATA[1.30×10 -5 ]]> 349 98.7 Example 2 <![CDATA[1.43×10 -5 ]]> 344 98.3 Example 3 <![CDATA[1.57×10 -5 ]]> 338 97.6 Example 4 <![CDATA[1.72×10 -5 ]]> 335 97.1 Example 5 <![CDATA[2.46×10 -5 ]]> 324 96.5 Example 6 <![CDATA[2.58×10 -5 ]]> 317 96.2 Example 7 <![CDATA[2.74×10 -5 ]]> 313 96.0 Example 8 <![CDATA[2.91×10 -5 ]]> 310 95.7 Example 9 <![CDATA[3.67×10 -5 ]]> 305 95.4 Example 10 <![CDATA[4.59×10 -5 ]]> 300 95.2 Comparative Example 1 <![CDATA[3.37×10 -4 ]]> 280 93.2 Comparative Example 2 <![CDATA[1.66×10 -4 ]]> 285 94.6 Comparative Example 3 <![CDATA[1.83×10 -4 ]]> 282 94.0 As can be seen from Examples 1-4 and Table 2, the high-efficiency charged cleaning and protective composite spray prepared in this application has excellent decontamination effect, insulation and volatility.
[0065] Combining Examples 1 and 9-10 with Table 2, it can be seen that, compared with Example 1, the high-efficiency charged cleaning and protective composite spray prepared in Examples 9-10 has reduced decontamination effect and volatility. This indicates that the addition of thiourea introduces sulfur element and prepares nitrogen-sulfur co-doped carbon quantum dots. The surface of these quantum dots introduces nitrogen- and sulfur-containing functional groups, which significantly enhances light absorption capacity. The carbon quantum dots are encapsulated in situ on the surface of porous materials, thereby efficiently converting absorbed light energy into heat energy, producing a local heating effect, forcibly accelerating the evaporation of residual liquid, and thus improving the evaporation rate of the cleaning composite spray.
[0066] Combining Example 1 and Comparative Example 1 with Table 2, it can be seen that compared with Example 1, the high-efficiency charged cleaning and protective composite spray prepared in Comparative Example 1 has reduced decontamination effect and reduced volatility. This indicates that the SiO2@ZIF-8 porous material can achieve slow release of low-carbon alcohols, providing time for preferential evaporation of fluorinated cosolvents, rapidly releasing adsorbed water molecules, ensuring thorough surface drying, and thus shortening the evaporation time.
[0067] Combining Example 1 and Comparative Examples 2-3 with Table 2, it can be seen that compared with Example 1, the high-efficiency charged cleaning and protective composite spray prepared in Comparative Example 1 has reduced decontamination effect and reduced volatility. This indicates that the ZIF-8 shell has a hydrophobic microporous structure, which has a selective preferential adsorption capacity for low-carbon alcohol molecules, while the mesoporous silica has a hydrophilic mesoporous structure, which has a strong adsorption affinity for water molecules. The two form a bilayer adsorption system with an outer hydrophobic and an inner hydrophilic structure, which achieves selective separation and stepwise adsorption of alcohol and water molecules. In the volatilization stage, the ZIF-8 shell utilizes its confinement effect, which is comparable to the size of low-carbon alcohol molecules, to exert a strong binding effect on the adsorbed low-carbon alcohol molecules, thereby achieving slow release regulation and shortening the volatilization time.
[0068] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-efficiency electrostatic cleaning and protective composite spray, characterized in that, Including the following parts by weight of raw materials: 20-40 parts of low carbon alcohol, 5-15 parts of nonionic surfactant, 0.1-0.3 parts of SiO2@ZIF-8 porous material, 1-3 parts of antistatic regulator, 0.05-0.2 parts of antioxidant stabilizer, and 40-75 parts of water.
2. The high-efficiency charged cleaning and protective composite spray according to claim 1, characterized in that, The preparation method of the SiO2@ZIF-8 porous material includes the following steps: S1. Disperse mesoporous silica in a zinc nitrate hexahydrate ethanol solution, stir and evaporate the solvent at 60-70℃, and calcine at 550-600℃ for 2-4 hours to obtain MSN-ZnO. The mass ratio of the mesoporous silica to the zinc nitrate hexahydrate ethanol solution is 1:35-45. S2. The MSN-ZnO and nitrogen-sulfur co-doped carbon quantum dots are dispersed in a 2-methylimidazolium methanol solution, stirred at 23-27°C, centrifuged, washed, and dried to obtain SiO2@ZIF-8 porous material. The mass ratio of MSN-ZnO to 2-methylimidazolium methanol solution is 1:500-700.
3. The high-efficiency charged cleaning and protective composite spray according to claim 2, characterized in that, The method for preparing the nitrogen-sulfur co-doped carbon quantum dots includes the following steps: Citric acid and thiourea were ultrasonically dissolved in N,N-dimethylformamide to prepare a transparent solution. The transparent solution was then subjected to a hydrothermal reaction at 180-200℃ for 12-16 hours. After filtration, dialyzing, and freeze-drying, nitrogen-sulfur co-doped carbon quantum dots were obtained.
4. The high-efficiency charged cleaning and protective composite spray according to claim 3, characterized in that, The mass ratio of citric acid, thiourea and N,N-dimethylformamide is 1:1.5-2:10-15.
5. The high-efficiency charged cleaning and protective composite spray according to claim 1, characterized in that, The low-carbon alcohol is selected from one or more of isopropanol, ethanol, n-propanol and methanol.
6. The high-efficiency charged cleaning and protective composite spray according to claim 1, characterized in that, The antistatic modifier is selected from one or more of cationic antistatic agents, amphoteric antistatic agents, and nonionic antistatic agents.
7. The high-efficiency charged cleaning and protective composite spray according to claim 1, characterized in that, The antioxidant stabilizer is selected from one or more of phenolic antioxidants, amine antioxidants, and thioether antioxidants.
8. The high-efficiency charged cleaning and protective composite spray according to claim 1, characterized in that, The nonionic surfactant is selected from one or both of fatty alcohol polyoxyethylene ethers and alkyl glycosides.
Citation Information
Patent Citations
Insulating electrified cleaning agent and preparation method thereof
CN120607927A